Pattern-reversal visual evoked potentials in prosthetic vision and simulated visual reduction - Sandra R Montezuma; Yingchen He; Jonathon Toft-Nielsen; Gordon Legge (BMJ Open Ophthalmology)
Objective To quantitatively evaluate visual evoked potentials (VEPs) in prosthetic vision and simulated visual reduction.Methods and analysis Four blind patients implanted with the Argus II retinal prosthesis and seven sighted controls participated. VEPs were recorded with pattern-reversal stimuli (2 cycles of a horizontal square wave grating, 0.1 cycle/degree) at 1.07 reversals per second (rps) for Argus II subjects and 3.37 rps for controls. Argus II patients had both eyes patched, viewing the pattern solely through their implant. Controls viewed the pattern monocularly, either with their best-corrected vision or with simulated visual reduction (field restriction, added blur or reduced display contrast).Results VEPs recorded in Argus II patients displayed a similar shape to normal VEPs when controls viewed the pattern without simulated visual reduction. In sighted controls, adding blur significantly delayed the P100 peak time by 8.7 ms, 95% CI (0.9, 16.6). Reducing stimulus contrast to 32% and 6% of full display contrast significantly decreased P100 amplitude to 55% (37%, 82%) and 20% (13%, 31%), respectively. Restriction on the field of view had no impact on either the amplitude or the peak latency of P100.Conclusion The early visual cortex in retinal prosthesis users remains responsive to retinal input, showing a similar response profile to that of sighted controls. Pattern-reversal VEP offers valuable insights for objectively evaluating artificial vision therapy systems (AVTSs) when selecting, fitting and training implant users, but the uncertainties in the exact timing and location of electrode stimulation must be considered when interpreting the results.